Polymer brushes interfacing blood as a route toward high performance blood contacting devices - Surman, František; Riedel, Tomáš; Bruns, Michael; Kostina, Nina Yu; Sedláková, Zdeňka; Rodriguez-Emmenegger, Cesar (Macromolecular bioscience, 2015)
In the current study, well-defined polymer brushes are shown as an effective surface modification to resist the adhesion of whole blood and its components. Poly[oligo(ethylene glycol)methylether methacrylate] (poly(MeOEGMA)), poly(hydroxyethyl methacrylate) (poly(HEMA)), poly[N-(2-hydroxypropyl) methacrylamide] (poly(HPMA)), and poly(carboxybetaine acrylamide) (poly(CBAA)) brushes were grown by surface initiated atom transfer radical polymerization (SI-ATRP) and subsequently characterized by Fourier-transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), dynamic contact angle measurements, atomic force microscopy (AFM), and surface plasmon resonance (SPR) spectroscopy. All brushes decreased the fouling from blood plasma over 95% and prevented the adhesion of platelets, erythrocytes, and leukocytes as evidenced by SPR and SEM measurements.
Keywords: plazma bohatá na destičky; povrchové vlastnosti; Spectroscopy, Fourier Transform Infrared; testování materiálů; polymerizace; Materials Testing; blood compatibility; voda; Biofouling; Photoelectron Spectroscopy; Platelet-Rich Plasma; Microscopy, Atomic Force; Polymers; buněčná adheze; mikroskopie atomárních sil; Blood; biokompatibilní potahované materiály; Coated Materials, Biocompatible; blood plasma; lidé; polymery; fotoelektronová spektroskopie; proteins; Humans; Polymerization; Surface Properties; surfaces; non-fouling; krev; bioznečištění; spektroskopie infračervená s Fourierovou transformací; Water; Cell Adhesion